2011
DOI: 10.1007/s11249-011-9792-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-Friction Coatings of Zinc Oxide Synthesized by Optimization of Crystal Preferred Orientation

Abstract: The crystal preferred orientation of zinc oxide (ZnO) coatings on stainless steel substrates was precisely controlled by a combinatorial sputter-coating system. ZnO coatings were analyzed by X-ray diffraction spectroscopy, and surface and interfacial cutting analysis methods. The frictional properties of the coatings in a vacuum, the atmosphere, oil of n-hexadecane, and oil doped with palmitic acid molecules were observed. Different frictional behaviors of the ZnO coatings were observed by varying the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In particular, zinc oxide has been used in many areas, such as catalysis, 14 - 16 gas sensors, 17 and recently as lubricants. 18 - 19 In our previous study we showed that ZnO nanoparticles coating of stainless steel archwires decreased friction during sliding within stainless steel brackets. 20 In another research, we tried to decrease friction between stainless steel wires and ceramic brackets by depositing ZnO nanoparticles on the wires but we found no significant differences between coated and uncoated wires.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, zinc oxide has been used in many areas, such as catalysis, 14 - 16 gas sensors, 17 and recently as lubricants. 18 - 19 In our previous study we showed that ZnO nanoparticles coating of stainless steel archwires decreased friction during sliding within stainless steel brackets. 20 In another research, we tried to decrease friction between stainless steel wires and ceramic brackets by depositing ZnO nanoparticles on the wires but we found no significant differences between coated and uncoated wires.…”
Section: Introductionmentioning
confidence: 98%
“…1). In this method, various time intervals (10,15,20,30,40,50, and 60 min) were chosen for coating the wires with ZnO nanoparticles. Coating of ZnO nanoparticle was confirmed by SEM images of the wires (Fig.…”
Section: Wet Chemical Synthesis Of Zno Nanoparticlementioning
confidence: 99%
“…[10] Before the application of the coated metallic wires and brackets, the biocompatibility and safety of the nanoparticles should be evaluated. Biocompatible nanomaterials especially zinc oxide nanoparticles, have been used in many areas such as in catalysis [11][12][13] , in gas sensors [14] , and recently as lubricants [15,16] . Complementarily, these nanoparticles have an added advantage of possessing antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen in particular has been extensively used for reducing the grain size of ZnO. For most oxides, epitaxial growth along the (0001) plane generates the lowest friction coefficient as it has the lowest energy of all the possible crystallographic orientations, which is also known to reduce friction [ 178 , 179 ]. The addition of noble metals such as silver and gold also causes these metals to precipitate along the grain boundary thus strengthening the grain boundaries.…”
Section: Ceramics In Tribology Researchmentioning
confidence: 99%